Head-to-head comparison of LNA, MPγPNA, INA and Invader probes targeting mixed-sequence double-stranded DNA. Issue 1 (4th November 2019) - Emehiser, Raymond G.; Hall, Eric; Guenther, Dale C.; Karmakar, Saswata; Hrdlicka, Patrick J.
Abstract : Double-stranded (ds) Invader and INA probes allow for efficient and specific recognition of mixed-sequence dsDNA targets, whereas recognition is less efficient and specific with single-stranded LNA-modified DNA strands and fully modified MP γPNAs. Abstract : Four probe chemistries are characterized and compared with respect to thermal denaturation temperatures ( T m s), thermodynamic parameters associated with duplex formation, and recognition of mixed-sequence double-stranded (ds) DNA targets: (i) oligodeoxyribonucleotides (ONs) modified with Locked Nucleic Acid (LNA) monomers, (ii) MP γPNAs, i.e., single-stranded peptide nucleic acid (PNA) probes that are functionalized at the γ-position with ( R )-diethylene glycol (mini-PEG, MP ) moieties, (iii) Invader probes, i.e., DNA duplexes modified with +1 interstrand zipper arrangements of 2′- O -(pyren-1-yl)methyl-RNA monomers, and (iv) intercalating nucleic acids (INAs), i.e., DNA duplexes with opposing insertions of 1- O -(1-pyrenylmethyl)glycerol bulges. Invader and INA probes, which are designed to violate the nearest-neighbor exclusion principle, denature readily, whereas the individual probe strands display exceptionally high affinity towards complementary DNA (cDNA) as indicated by increases in T m s of up to 8 °C per modification. Optimized Invader and INA probes enable efficient and highly specific recognition of mixed-sequence dsDNA targets with self-complementary regions ( C 50 = 30–50 nM), whereas recognition is less efficient with LNA-modified ONs and fully modified MP γPNAs due to lower cDNA affinity (LNA) and a proclivity for dimerization (LNA and MP γPNA). A Cy3-labeled Invader probe is shown to stain telomeric DNA of individual chromosomes in metaphasic spreads under non-denaturing conditions with excellent specificity.